Pengaruh Leverage, Pertumbuhan Perusahaan, dan Keputusan Investasi Terhadap Nilai Perusahaan (Studi Pada SubSektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Lolita Permata Adella; Rahmaita, Rahmaita (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This research aims to determine the effect of leverage as proxied by debt to assets ratio (DAR), company growth as proxied assets growth (AG), and investment decisions as proxied by capital expenditure to book value off assets (CAP/BVA) on company value as proxied by price to book value (PBV). This type of research is quantitative research. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. Based on the purposive sampling method, a sample of 26 food and beverage companies was obtained. Research data was taken for 5 years, namely 2019-2023, so that sample data of 130 was obtained. Data was collected based on annual reports and company financial reports. Partial Least Square (PLS) is used as a method to analyze the data obtained. The results of the hypothesis test show that leverage has a positive and significant effect on company value, while company growth and investment decisions have no effect on company value.